Achieving a shared understanding in the creative industries : freelancers' use of boundary objects in collaborative innovation projects - Gonzalez-Cristiano, Alberto (Taylor & Francis, 2025)
This paper examines how freelancers in the field of the creative industries capture and distil their clients' needs and wants in collaborative innovation projects. Our empirical data from sixteen collaborative product-development processes led by freelancers in Finland and Spain allowed us to identify that boundary objects were critical for the achievement of a shared understanding at the beginning of the development process. In the later stages, the use of these objects decreased drastically and dialogue became the focus. The existence of a project match - whether the project was relevant and interesting for the freelancer - and a personal match - perceived similarity with the client in terms of thought and sense-making processes - were crucial to ensure engagement. From a managerial perspective, this paper stresses the importance of finding a personal and project match, highlights the role of boundary objects to create a shared understanding and reinforces the importance of dialogue in development processes and collaborative innovation.